Anti-benzo(a)pyrene diolepoxide: DNA adduct levels in peripheral mononuclear cells from coke oven workers and the enhancing effect of smoking - Rojas, Margarita; Alexandrov, Kroum; Auburtin, Guy; Wastiaux-Denamur, Agnès; Mayer, Lucienne; Mahieu, Bernard; Sebastien, Patrick; Bartsch, Helmut (Carcinogenesis, 1995)
The level of (±)-r-7, t-8-dihydroxy-t-9, 10-oxy-7,8,9,10-tetrahydrobenzo[a]pyrene (anti-BPDE) bound to DNA of lymphocytes plus monocytes in 39 coke oven workers exposed to polycyclic aromatic hydrocarbons (PAH) and 39 non-exposed persons (controls) were investigated, each of the groups consisting of smokers and non-smokers. The adduct level was measured by an improved HPLC/fluorescence method (Rojas, M., Alexandrov, K., van Schooten, F.J., Hillebrand, M., Kriek, E. and Bartsch, H., Carcinogenesis, 15, 557-560, 1994) through the release of the corresponding benzo[a]pyrene (B[a]P) tetrols. The anti-BPDE-DNA adduct was detected in 51% of coke oven workers exposed to PAH and in 18% of the non-exposed (control) subjects. The mean level of anti-BPDE-DNA adducts/108 nucleotides in coke oven workers (15.7 ± 37.8) was ∼8 times higher than in non-exposed subjects (2.0 ± 8.7). The interindividual variation of adduct levels was ∼ 100-fold in coke oven workers and ∼50-fold in controls respectively. Smokers in the exposed group had 3.5 times more DNA adducts than non-smokers. With the exception of one non-smoker with very high adduct levels (52.8 adducts/108), the control subjects showed the presence of barely detectable adducts in only 16% of the samples examined. The increased in vivo formation in some smokers and high variability of anti-BPDE-DNA adducts in coke oven workers suggests variations in genetically controlled activation/inactivation reactions of PAH metabolism.
Im Titel steht (a) in eckiger Klammer
Gesehen am 11.01.2024